Pengaruh Financial Distress, Perencanaan Pajak, dan Kualitas Audit Terhadap Manajemen Laba - Wulan Rizqi Nur Amaliyah; Hexana Sri Lastanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the effect of financial distress, tax planning, and audit quality on earnings management in real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. A quantitative approach is used with a purposive sampling method, utilizing financial statement data. Financial distress is measured using Altman Z-Score, tax planning with Tax Retention Rate (TRR), and audit quality through percentage ratio results based on industry specialization criteria (SPEC). The results show that financial distress has a significant positive effect on earnings management, while tax planning and audit quality have varying impacts. The study recommends strict supervision of earnings management practices, especially in companies with financial distress. Regulators are advised to strengthen audit and taxation policies to increase transparency, while academics can continue research on other sectors or periods for more in-depth results.